Effects of hydrogen and helium dilution on the optical band gap and photoluminescence of DC PECVD hydrogenated amorphous carbon films - Awang, R.; Rahman, Saadah Abdul (Penerbit Universiti Kebangsaan Malaysia, 2008)
A series of hydrogenated amorphous carbon (a-C:H) thin films were deposited using home-built direct-current (DC) plasma enhanced chemical vapour deposition (PECVD) system. The a-C:H thin films were deposited using pure methane (CH 4) gas diluted either with hydrogen (H) or helium (He). The effects of hydrogen and helium dilution on the photoluminescence (PL) properties and optical band gap (E-04) were studied. The dependence of PL properties and optical energy gap on the film thickness has also been investigated. The characterization techniques used were optical transmission and photoluminescence spectroscopies. The sp(2) cluster sizes were determined from Raman spectra are in the range of 5 to 7 nm. Hydrogen and helium. dilution of methane strongly influences the PL efficiency of the a-C:H films. The PL efficiency are enhanced with increase in film thickness for a-C:H films prepared both from H and He diluted CH4. The optical energy gap of these films decreases with increase in H or He dilution and film thickness.